PENERAPAN FIVE-FINGER RELAXATION TECHNIQUE UNTUK MENURUNKAN ANXIETY PADA PASIEN STROKE NON-HEMORAGIK: APPLICATION OF THE FIVE-FINGER RELAXATION TECHNIQUE TO REDUCE ANXIETY IN NON-HEMORRHAGIC STROKE PATIENTS - Nora Ngaji Pige, Delsiana; Dwi Retnani Putri Santoso, Shelfi; Paju, Wanto; Agustine, Uly (WELL BEING, 2025)
Background: Stroke is one of the leading causes of death and disability worldwide. The most common type of stroke is non-hemorrhagic stroke, which is a disruption in blood flow to the brain due to a blockage that causes brain tissue damage. Non-hemorrhagic stroke patients often experience anxiety due to physical and mental changes, as well as uncertainty about the healing process. One non-pharmacological intervention that can reduce anxiety levels is the five-finger relaxation technique. Objective: To describe the application of the five-finger relaxation technique to reduce anxiety levels in non-hemorrhagic stroke patients. Methods: This descriptive study used a case study method on two non-hemorrhagic stroke patients with anxiety at Waikabubak Regional Hospital. The intervention was administered for three days. Results: Patient 1 showed a decrease in respiratory rate from 24x/minute to 20x/minute, blood pressure from 160/97 to 135/87 mmHg, and anxiety score from 51 (moderate) to 38 (mild). The patient looked more relaxed, enthusiastic, comfortable, and no tremors. Patient 2 showed a decrease in respiratory rate from 23x/minute to 18x/minute, blood pressure from 157/95 to 130/70 mmHg, and anxiety score from 53 (moderate) to 42 (mild). The patient looked calmer and less pale. Conclusion: The five-finger relaxation technique is effective in reducing anxiety and stabilizing vital signs, especially respiratory rate, in non-hemorrhagic stroke patients by calming the nervous system, this therapy helps patients feel calmer and supports the healing process without interfering with other medical therapies. Suggestion: The application of the five-finger relaxation technique should be done if feeling anxious and stressed to reduce anxiety in non-hemorrhagic stroke patients.